Superpredation increases mercury levels in a generalist top predator, the eagle owl - Lourenço, Rui (2012)
Superpredation can increase the length of the food chain and potentially lead to mercury (Hg) bioaccumulation in top predators. We analysed the relationship of Hg concentrations in eagle owls Bubo bubo to diet composition and the percentage of mesopredators in the diet. Hg levels were measured in the adult feathers of eagle owls from 33 owl territories in the south-western Iberian Peninsula, and in three trophic levels of their prey: primary consumers, secondary consumers and mesopredators. In addition, we studied 6,181 prey in the eagle owl diet. Hg concentrations increased along the food chain, but the concentrations in eagle owls showed considerable variation. The Hg concentration in eagle owls increased when the percentage of mesopredators in the diet increased and the percentage of primary consumers decreased. Superpredation is often related to food stress, and the associated increase in accumulation of Hg may cause additional negative effects on vertebrate top predators. Hg levels in these eagle owl populations are relatively low, but future monitoring is recommended.